The Ethical Significance of the Consequences of Our Actions: Contemporary Theory of Action, Aquinas, and the Utilitarian Point of View - Stefan Hofmann (Warszawskie Studia Teologiczne)
Human actions have consequences for others and for oneself. The consequences may be positive. They may, however, also be devastating. This is why it is important for the moral evaluation of actions to take their consequences into account. The ethical significance of the consequences may depend on many aspects: From the point of view of action theory, ethicists may distinguish different kinds of consequences, like intended/unintended or foreseen/unforeseen consequences. From the point of view of normative ethics, scholars give different ethical weight to the consequences. This paper tries to combine insights from both disciplines: In section 1, I present a view of the consequences which draws heavily on contemporary theory of action. In section 2, I compare the normative accounts of three exemplary moral philosophers: the act utilitarian theory of John J. C. Smart, the rule utilitarian account of Richard Brandt, and the scholastic approach of Thomas Aquinas. I argue that we should give different moral weight to different kinds of consequences. It is shown that when it comes to complex actions, Aquinas’ account is more sophisticated and has more intuitive support than its utilitarian rivals.